Integrated hip fracture care pathway (IHFCP): reducing complications and improving outcomes - Louise Heyzer; Rani Ramason; Joseph Antonio De Castro Molina; William Wai Lim Chan; Chen Yi Loong; Ernest Beng Kee Kwek (Singapore Medical Journal)
Introduction: Hip fractures in elderly people are increasing. A five-year Integrated Hip Fracture Care Pathway (IHFCP) was implemented at our hospital for seamlessly integrating care for these patients from admission to post discharge. We aimed to evaluate how IHFCP improved process and outcome measures in these patients. Methods: A study was conducted over a five-year period on patients with acute fragility hip fracture who were managed on IHFCP. The evaluation utilised a descriptive design, with outcomes analysed separately for each of the five years of the programme. First-year results were treated as baseline. Results: The main improvements in process and outcome measures over five years, when compared to baseline, were: (a) increase in surgeries performed within 48 hours of admission from 32.5% to 80.1%; (b) reduced non-operated patients from 19.6% to 11.9%; (c) reduced average length of stay at acute hospital among surgically (from 14.0 ± 12.3 days to 9.9 ± 1.0 days) and conservatively managed patients (from 19.1 ± 22.9 to 11.0 ± 2.5 days); (d) reduced 30-day readmission rate from 3.2% to 1.6%; and (e) improved Modified Functional Assessment Classification of VI to VII at six months from 48.0% to 78.2%. Conclusion: The IHFCP is a standardised care path that can reduce time to surgery, average length of stay and readmission rates. It is distinct from other orthogeriatric care models, with its ability to provide optimal care coordination, early transfer to community hospitals and post-discharge day rehabilitation services. Consequently, it helped to optimise patients’ functional status and improved their overall outcome.